Development of the Research in Isoflavones - Mini Review - Chang, Hsiang; Lin, Hsin-Cheng; Chang, Yu-An (Asian Journal of Chemistry, 2012)
Isoflavones show a variety of biological functions, including distinct antitumor activity and reducing the incidence of cardiovascular disease. According to previous studies, this review summarized the development of the pharmacological effects and synthesis of isoflavones.